2011
DOI: 10.1210/jc.2010-2460
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Emptying, Incretin Hormone Secretion, and Postprandial Glycemia in Cystic Fibrosis—Effects of Pancreatic Enzyme Supplementation

Abstract: Pancreatic enzyme supplementation plays an important role in incretin secretion, gastric emptying, and postprandial hyperglycemia in CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
0
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 19 publications
7
76
0
8
Order By: Relevance
“…In a small study of adults with CF we demonstrated rapid emptying of a high fat/ carbohydrate meal, associated with marked postprandial hyperglycaemia. Pancreatic enzyme supplementation slowed gastric emptying and markedly decreased the postprandial glycaemic excursion ( Fig.1-2) [41]. We recently reported the same phenomenon in a study of 14 paediatric CF patients (Fig.3) [45].…”
Section: Gastric Emptying In Health and Cfmentioning
confidence: 53%
See 4 more Smart Citations
“…In a small study of adults with CF we demonstrated rapid emptying of a high fat/ carbohydrate meal, associated with marked postprandial hyperglycaemia. Pancreatic enzyme supplementation slowed gastric emptying and markedly decreased the postprandial glycaemic excursion ( Fig.1-2) [41]. We recently reported the same phenomenon in a study of 14 paediatric CF patients (Fig.3) [45].…”
Section: Gastric Emptying In Health and Cfmentioning
confidence: 53%
“…Despite the potential importance of abnormal gastric emptying in CF patients, only a limited number of studies have evaluated gastric emptying in this population [33,[41][42][43][44][45], with inconsistent results, attributable to differences in subject characteristics, meal composition, use of pancreatic enzymes and the method used to measure gastric emptying. Studies have reported abnormally rapid [41,42] or delayed [44] emptying, or no difference from controls [33,43,45].…”
Section: Gastric Emptying In Health and Cfmentioning
confidence: 99%
See 3 more Smart Citations